Analisis Tiga Bentuk Ukuran ROI terhadap Nilai ADC pada Kasus Hepatocellular Carcinoma - Widiatmoko, Mahfud Edy; Tarigan, Asumsie; Widayadi, Widayadi (Poltekkes Kemenkes Semarang, 2025)
Background: Hepatocellular Carcinoma (HCC) is the third leading cause of death in the world. One important aspect of lesion measurement in predicting HCC grading on Magnetic Resonance images is the ADC value obtained by performing Region of Interest can be a variation in shape size of Freehand, Circle, or Point voxel.Methods: Analytical quantitative research by comparing three shapes sizes ROI on the value of ADC in cases of HCC. Data was collected at the Radiology Installation of hospitals in Jakarta from 50 patients who underwent liver MRI with DWI-ADC Map images between January and October 2023. Analysis of data using Friedman test statistical test followed by Dunnet post hoc test.Results: ADC value for Freehand ROI was 1.33x10-3 mm2/s, Circle ROI was 1.31x10-3 mm2/s and Point Voxel ROI was 1.23x10-3 mm2/s. The statistic p0.05 means that there is a significant difference in ADC values between Point Voxel and Freehand and Circle ROI.Conclusions: ROI with different size shapes (Freehand, Circle, Point Voxel) affects ADC value. Circle ROI is recommended to evaluate HCC because the placement of the ROI can avoid inhomogeneous areas when measuring the ADC value on an MRI of the Liver with Hepatocellular Carcinoma.